Probing structural changes during amyloid aggregation of the sweet protein MNEI. (20th December 2019) - Donnarumma, Federica; Leone, Serena; Delfi, Masoud; Emendato, Alessandro; Ami, Diletta; Laurents, Douglas V.; Natalello, Antonino; Spadaccini, Roberta; Picone, Delia
Abstract : Protein self‐assembly is a ubiquitous phenomenon, traditionally studied for its links to amyloid pathologies, which has also gained attention as its physiological roles and possible biotechnological applications emerged over time. It is also known that varying the conditions to which proteins are exposed can lead to aggregate polymorphism. To understand the factors that trigger aggregation and/or direct it toward specific outcomes, we performed a multifaceted structural characterization of the thermally induced self‐assembly process of MNEI, a model protein able to form amyloid aggregates under nondenaturing conditions. MNEI is also known for its extreme sweetness which, combined with a considerable thermal stability, makes the protein a promising alternative sweetener. Fourier‐transformed infrared spectroscopy and electron microscopy data showed that the presence of NaCl accelerates the kinetics of fibrillar aggregation, while disfavoring the population of off‐pathway states that are instead detected by native gel electrophoresis at low ionic strength. NMR studies revealed how NaCl modulates the self‐assembling mechanism of MNEI, switching the process from soluble oligomeric forms to fibrils. Comparative analysis demonstrated that the presence of NaCl induces local differences in the protein dynamics and surface accessibility, without altering the native fold. We identified the regions most affected by the presence of NaCl, which control the aggregation process, and represent hot spots on the protein surface for the rational design of new mutants with controlled aggregation propensity. Abstract : The sweet protein MNEI, often used as a model for folding studies, forms amyloid aggregates at acidic pH. We demonstrate that fibrils form under nondenaturing conditions and that NaCl greatly accelerates the process through changes in the protein surface dynamics. This disfavors the population of off‐pathway oligomeric and partially unfolded states, which are instead detected at low ionic strength.